1978
DOI: 10.1111/j.1365-2389.1978.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Soil Variability for Forest Soil Studies in North‐east Scotland

Abstract: A study of 13 sample plots (0.01 ha) in 6 forests showed that the average number of topsoil samples required per plot to secure 95 per cent confidence limits for a range about the mean of + l o per cent was 6 for total nitrogen, 9 for total phosphorus and 29 for 0.5 M acetic acid extractable nutrients (calcium, magnesium, phosphorus and potassium). In some plots 95 per cent confidence intervals, based on 5 composite samples. for extractable nutrients were as large as the range of mean values for different plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…A study of thirteen 0.01 ha plots in North East Scotland showed that the variability of different properties was not uniform, and that to estimate the mean at the 95% confidence limit with a range about the mean of ±10% the number of sampling points required ranged from 6 for total N to 29 for Ca, P, Mg and K (Blyth and MacLeod, 1978). The number required for the Level II study will vary, therefore, from site to site.…”
Section: Introductionmentioning
confidence: 97%
“…A study of thirteen 0.01 ha plots in North East Scotland showed that the variability of different properties was not uniform, and that to estimate the mean at the 95% confidence limit with a range about the mean of ±10% the number of sampling points required ranged from 6 for total N to 29 for Ca, P, Mg and K (Blyth and MacLeod, 1978). The number required for the Level II study will vary, therefore, from site to site.…”
Section: Introductionmentioning
confidence: 97%
“…The extent of compaction, initial bulk density, depth of impact, and subsequent soil recovery are all factors that determine the consequences of timber harvesting or site preparation on productivity. In addition, duration and variability of compaction can be significant from site to site or at depth in the soil profile (Beckett and Webster 1971;Blythe and Macleod 1978;Courtin et al 1983). For instance, variability within soil textural groups, forest stands, or on skid trails can be as great as or greater than the variability between them (Courtin et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…An allowable error of 10% at 95% confidence is normally considered acceptable (Blyth and Macleod 1978). Also calculated were the number of samples required for the same confidence level but with a greater allowable error.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This is particularly true for assessment of timber production from known relationships between tree growth and site attributes (Blyth and Macleod 1978). According to Hedley and Kang (1972), one major problem in quantifying the ecological role of forest soil in terms of averages for nutrient contents in the tropics, particularly on recently cleared land, is the high degree of soil variability, which results in uneven crop growth.…”
mentioning
confidence: 99%